2008
DOI: 10.1177/112067210801800306
|View full text |Cite
|
Sign up to set email alerts
|

Mooren's Ulcer following Extracapsular Cataract Extraction

Abstract: Mooren''s ulcer may occur following extracapsular cataract extraction and when it does it is most likely to be unilateral and contiguous with the wound. These findings support the notion that exposure of normally concealed corneal antigens may contribute to the pathogenesis of Mooren''s ulcer in some patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Corneoscleral incisions, particularly those related to extra capsular cataract extraction, have been specifically implicated in the pathogenesis of MU. A recent study investigating the relationship between MU and prior cataract extraction found that the ulceration in patients with prior extracapsular cataract extraction was typically unilateral, developed within 2 years of the cataract surgery and occurred at or contiguous with the cataract wound, which was typically a superior limbal incision in the majority of cases [12,21].…”
Section: Risk Factorsmentioning
confidence: 98%
“…Corneoscleral incisions, particularly those related to extra capsular cataract extraction, have been specifically implicated in the pathogenesis of MU. A recent study investigating the relationship between MU and prior cataract extraction found that the ulceration in patients with prior extracapsular cataract extraction was typically unilateral, developed within 2 years of the cataract surgery and occurred at or contiguous with the cataract wound, which was typically a superior limbal incision in the majority of cases [12,21].…”
Section: Risk Factorsmentioning
confidence: 98%
“…This is supported by the fact that their cases healed after limbal conjunctivectomy. However, Acharya et al, [5] in a retrospective study of patients who had extracapsular cataract extraction in Madurai, India, concluded that exposure of normally concealed antigens may contribute to the pathogenesis of MU in some patients. Zelefsky et al [6] demonstrated an association between MU and human leucocyte antigen (HLA) type DR17(3) in patients from Tamil Nadu state of south India.…”
Section: Introductionmentioning
confidence: 95%